Il diritto alla disconnessione nella prospettiva italiana e comparata - Rosa Di Meo (Labour & Law Issues, 2017)
A few months after the Loi Travail of the 2016, italian parliament also intervened to foresee the disconnection from technological instruments that make it possible job performance. However, unlike French legislature, italian language doesn't expressly express the disconnection as a right, so it's necessary to analyze the French legislation for undertand the differences between a different type of data offered by the Italian parliament. Paper analyze others questions around a not referenced at the disconnection as right in order to allow a "real" work-life balance and prevent that disconnection from being modulated on downtime of the company and not the employeers. In this perspective the paper hopes for an intervention of collective bargaining and a new possible applications of article 2087 c.c.